Peran self-control dalam prokrastinasi akademik pada siswa pendidikan vokasional - Vine Apriliani; Siti Fitriana; Venty Venty (Jurnal Konseling dan Pendidikan, 2026)
Academic procrastination is a common problem among students and may negatively affect academic achievement and task completion. Self-control is considered one of the psychological factors associated with this behavior. This study analyzed the relationship between self-control and academic procrastination among Grade XI students at SMK Negeri 9 Semarang. This study employed a quantitative cross-sectional correlational design involving 167 students selected through simple random sampling from a population of 319 students. Data were collected using self-control and academic procrastination questionnaires developed from established theoretical constructs and measured using a five-point Likert scale. The instruments demonstrated acceptable validity and reliability (Cronbach's alpha and construct validity: isi sesuai hasil pengujian instrumen). Data were analyzed using Pearson Product Moment correlation. The findings revealed a significant relationship between self-control and academic procrastination (r = 0.332; p < 0.001). The results indicate that self-control is associated with students' tendency to procrastinate in completing academic tasks, although the strength of the relationship is relatively low. These findings suggest that strengthening students' self-control may support efforts to reduce academic procrastination through guidance and counseling programs in vocational schools.